Effort to increase an engine performance using electrical ignition system for motor vehicle - Bandem Adnyana, I Wayan (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009)
Increasing engine performances using electrical ignition system on motor vehicle. In accordance with the development oftechnology, improvisation of automotive is created in order to increase the performance of engine. The method to increase thisperformance has been done by modify the ignition system, where the conventional method of ignition system which uses contactbreaker substituted by using capacitor. The improvisation of ignition system has been tested by increasing the speed and load onstationary condition. Results show that the improvisation of ignition system by using capacitor increases the effective power andreduce the specific fuel consumption of engine and reduce the gas emission of CO.
Keywords: Ignition system, Capacitor, Engine performance